2021
DOI: 10.1200/jco.20.02015
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Controlled Trial of eRAPID: eHealth Intervention During Chemotherapy

Abstract: PURPOSE Electronic patient self-Reporting of Adverse-events: Patient Information and aDvice (eRAPID) is an online eHealth system for patients to self-report symptoms during cancer treatment. It provides automated severity-dependent patient advice guiding self-management or medical contact and displays the reports in electronic patient records. This trial evaluated the impact of eRAPID on symptom control, healthcare use, patient self-efficacy, and quality of life (QOL) in a patient population treated predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(224 citation statements)
references
References 39 publications
13
209
1
1
Order By: Relevance
“…The current pandemic represents an opportunity to further boost use of digital health technologies in the hematology arena and maximize the use of remote ePRO data collection in patients with hematologic malignancies. As recently observed, the COVID-19 pandemic has precipitated a shift to remote technology-enabled care [24].…”
Section: Study Rationale and Hypothesesmentioning
confidence: 88%
See 1 more Smart Citation
“…The current pandemic represents an opportunity to further boost use of digital health technologies in the hematology arena and maximize the use of remote ePRO data collection in patients with hematologic malignancies. As recently observed, the COVID-19 pandemic has precipitated a shift to remote technology-enabled care [24].…”
Section: Study Rationale and Hypothesesmentioning
confidence: 88%
“…Similarly, another RCT in patients with advanced-stage lung cancer showed that a web-mediated follow-up algorithm based on self-reported symptoms also improved overall survival [23]. A more recent RCT conducted in patients with solid cancer, who were mainly treated with curative intent, showed that real-time monitoring with ePROs improved physical well-being and self-efficacy without increasing hospital workload, and authors concluded that online symptom monitoring is a feasible approach to be implemented in routine care [24].…”
Section: The Added Value Of Patient-reported Outcome Assessment In Routine Cancer Carementioning
confidence: 99%
“… 33 However, no significant difference was recorded at 18 weeks between the two arms of the study ( p = 0.699). 33 …”
Section: Evidence To Support the Use Of Eproms In Routine Clinical Carementioning
confidence: 89%
“…Conversely, in the United Kingdom (UK), the RCT of the eRAPID system by Absolom et al did not find any significant difference in the utilisation of healthcare resources between the intervention and control arms. 33 Specifically, there were no significant differences in chemotherapy delivery, hospital admissions, acute oncology assessments or emergency hotline calls. 33 …”
Section: Evidence To Support the Use Of Eproms In Routine Clinical Carementioning
confidence: 91%
See 1 more Smart Citation